METODE ELEMEN HINGGA LEAST SQUARE RUANG-WAKTU UNTUK PERSAMAAN KONVEKSI-DIFUSI - , Desy Purnami S. P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this final task, we consider the model of transport phenomena occurs in fluids known as cenvection-diffution equations. To solve the model numerically we use the least square finite element method (LSFEM). The LSFEM is based on minimization of residuals in a least-squares sense. The computational code was applied in the solution of one-dimensional and two-dimensional convection-diffution problems.